Political Metaphor in the Life of the Buddha - Tilakaratne, Asanga (University of Colombo, 2010)
The legend says that the Brahmins who were called by Suddhodana, the father of Siddhartha, the future Buddha, to predict his new born child’s future said that either he will become universal monarch if he were to remain in the worldly life or he will be Fully Enlightened One if he were to renounce the worldly life. Although one of them was certain that the prince will renounce household life and become the Buddha, the point behind the legend is that the concept of universal monarch or the concept kingship has been associated with the life of the Buddha in a very vivid manner from its very beginning. The Buddha has been described as the king of Dhamma (dhamma-raja), and his mission has been described as ‘the turning of the wheel of Dhamma’ (dhamma-cakkapavattana). It is interesting to see how the Buddha’s life and mission has been compared to that of an all powerful monarch. The purpose of this paper is to examine this very strong political metaphor in the life of the Buddha. Although Rhys Davids, a pioneering Pali Buddhist scholar, noticed the significance of this metaphor as far back as the turn of the last century, he was of the opinion that this was a result of the over-enthusiasm of later disciples. In this paper I would like to propose that this metaphor is not a mere later development but has its roots in the very life of the Buddha who was brought up in a ‘political’ atmosphere, perhaps with his own political ambitions